Method of obtaining an organic polycrystalline scintillator for detecting beta-radionuclide sources in natural waters - Andryushchenko, A.Yu.; Belikov, K.N.; Galunov, N.Z.; Martynenko, E.V.; Lazarev, I.V.; Polupan, Ya.I.; Tarasenko, O.A. (Functional Materials, 2018)
The method of producing an organic polycrystalline scintillator with two-stage sorbent filled holes for detecting beta-emitting source of <f2m^>90Sr in natural water is proposed. That confirms that synthetic hydroxylapatite is the optimal sorbent to solving the problem. For the polycrystalline scintillator of p-terphenyl doped by 1,4-diphenylbutadiene-1,3 which has the holes filled with hydroxylapatite as a sorbent, the efficiency of detecting beta particles of 90Sr isotope sorbed from the water sample reaches 90 %.